EFFECTIVENESS OF MULLIGAN’S BENT LEG RAISE AND TWO LEG ROTATION TECHNIQUES TO IMPROVE HAMSTRING FLEXIBILITY IN RECREATIONAL FOOTBALL PLAYERS (International Journal of Food and Nutritional Sciences, 2021)
The purpose of this investigation was to find out the effectiveness of Mulligan’s bent leg raise and two leg rotation techniques to improve hamstring flexibility in recreational football players. A total number of 40 football players between the age group of 18 to 28 years were recruited in the study according to the inclusion and exclusion criteria. Statistical analysis of data using the “Statistical Package for the Social Sciences” (SPSS) version 22.0 as quantitative tool were utilized for all statistical procedures.The values when compared between the groups were t = 3.101, p = 0.0044, found in post Two Leg Rotation v/s Bent Leg Raise on Right limb and t= 2.632, p = 0.0137, was in post Two Leg Rotation v/s Bent Leg Raise on Left limb, respectively using unpaired t-test, hence considered significant.